Conducting a consensus conference to design a psychology service model for acute mental health wards. (17th June 2020) - Raphael, Jessica; Haddock, Gillian; Edge, Dawn; Lovell, Karina; Bucci, Sandra; Winter, Rachel; Drake, Richard; Price, Owen; Berry, Katherine
Abstract : Objectives: This paper outlines best practice recommendations for the clinical psychologist's role in inpatient settings and also presents a methodology for deriving evidence‐based recommendations, which may be replicated by health care professionals in other areas of service development. Methods: Twenty‐three, nationally drawn experts, deemed expert by profession and/or experience attended a one‐day conference. Participants were presented with findings from previous research and key unanswered questions in terms of how psychological services should be delivered in inpatient settings. Participants discussed the information presented within small groups and then independently responded to the questions posed. Responses to questions either involved ranking priorities or choosing the best possible option in terms of what or how aspects of the model should be delivered. Results: We were able to identify referral priorities for formulation, nurse‐led psychosocial interventions and psychological therapy using ranking questions. Consensus (defined as 70% agreement) was achieved within 1–3 voting rounds for all questions which involved selecting one of a range of possible options. These responses provided information about how to deliver formulation, supervision of nurse‐led psychosocial interventions, staff well‐being interventions, and one‐to‐one therapy, as well as psychologists' own training and supervisions needs. Conclusions: Findings provide recommendations relating to five different service areas for inpatient settings seeking to implement a psychological service model: formulation, nurse‐led interventions, one‐to‐one therapy, staff well‐being, and psychologist training and supervision. Additionally, we showcase a methodology for synthesizing knowledge and decision‐making that can be implemented by researchers and health care professionals seeking to design interventions or service models in other settings. Practitioner points: Psychologists working on inpatient wards should endeavour to develop a team formulation for each patient, prioritizing patients with longer length of stay, repeated admissions, and who staff find challenging. Psychologists should offer 1:1 therapy with patients who have complex needs that cannot be addressed by nurse‐led interventions. Reflective practice sessions should be a key component of the psychologist's role on inpatient wards with the function of improving staff well‐being. Consensus conferences are useful methodology to synthesize knowledge and undertaking decision‐making in relation to the design of interventions or service models.